ISOLATION OF MANGIFERIN AND IT'S ANTIVIRAL EVALUATION - E.SHANMUGAPRIYA,; DR.V.RAVICHANDIRAN,; DR.M.VIJEYAANANDHI, (International Journal of Pharma and Bio Sciences, 2016)
Mangiferin is a natural occurring xanthone C-glucoside. Mangiferin, (1, 3, 6, 7-tetrahydroxy xanthone- C2-b- D glucoside) has been isolated from various parts of Swertia chirata. Mangiferin is a pharmacologically active phytochemical present in large amount in bark, fruits, roots and leaves of Mangifera indica.The present work is aimed to isolate mangiferin by column chromatography from the ethanolic extract of various parts of Swertia chirata and assess its antiviral activity. The conclusive structure of the isolated compound was established using TLC, HPLC, UV/VIS, FTIR and NMR spectral analysis. In vitro antiviral activity of the isolated mangiferin was studied. The present study confirms the antiviral effect of the isolated mangiferin which could be further processed for its development as an antiviral agent.